PENGGUNAAN RUMPUT AZOLLA SEBAGAI BAHAN ALTERNATIF DALAM KONTEKS PERTANIAN TERPADU SECARA BERKELANJUTAN : LITERATURE REVIEW - Jerius Wende; Yohanes Freadyanus Kasi (Jurnal Inspirasi Peternakan, 2026)
Azolla is an aquatic fern with a high protein content and potential use as an alternative material in sustainable integrated farming systems. This study aims to examine and analyze existing research on the use of azolla grass as an alternative material in the context of sustainable integrated farming. The research method used was a literature review, analyzing 25 published scientific journals obtained through Google Scholar. The study's findings examined various research findings related to the use of azolla in sustainable integrated farming systems. The results indicate that azolla can improve feed efficiency, growth, and productivity of livestock and fish. Furthermore, azolla also functions as a green manure, improving soil fertility, reducing chemical fertilizer use, and lowering production costs. Based on the review of various journals, it can be concluded that numerous studies have been conducted on the use of azolla as an alternative material in the context of sustainable integrated farming. Further research is needed on the use of azolla grass as an alternative material to support sustainable integrated farming systems in Nagekeo Regency.